2017
DOI: 10.1038/s41598-017-10892-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intensive Blood Pressure Reduction on Acute Intracerebral Hemorrhage: A Systematic Review and Meta-analysis

Abstract: Current opinions about the effect of intensive blood pressure (BP) reduction for acute intracerebral hemorrhage (ICH) are inconsistent. We performed a meta-analysis to evaluate the efficacy and safety of intensive BP reduction for acute ICH by analyzing data from several recent randomized controlled trials (RCTs). There were six eligible studies that met the inclusion criteria, for a total of 4,385 acute ICH patients in this meta-analysis. After analyzing these data, we found differences between intensive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Meta-analyses of these trials and other smaller studies showed that early intensive blood pressure lowering was safe, but without functional or mortality benefit. 78–82 In contrast, a linear association between systolic blood pressure achieved in the first 24 hours and functional status was found in a recent individual participant data meta-analysis of the two largest trials, with improvements in functional recovery seen for blood pressure as low as 120–130 mm Hg. 83 These trials excluded patients with large and severe haematomas, however, so caution must be exercised when treating such patients, especially where large reductions in very hypertensive patients might predispose to harm.…”
Section: Acute Managementmentioning
confidence: 95%
“…Meta-analyses of these trials and other smaller studies showed that early intensive blood pressure lowering was safe, but without functional or mortality benefit. 78–82 In contrast, a linear association between systolic blood pressure achieved in the first 24 hours and functional status was found in a recent individual participant data meta-analysis of the two largest trials, with improvements in functional recovery seen for blood pressure as low as 120–130 mm Hg. 83 These trials excluded patients with large and severe haematomas, however, so caution must be exercised when treating such patients, especially where large reductions in very hypertensive patients might predispose to harm.…”
Section: Acute Managementmentioning
confidence: 95%
“…Hypertensive cerebral haemorrhage accounts for 21 ~ 48% of all stroke patients, among which basal nucleus haemorrhage is the most common symptom, representing approximately 50% of cerebral haemorrhage patients [ 1 , 2 ]. Patients often have symptoms, such as hemianopia, hemiplegia and hemiparesthesia, because the conduction bundle in the basal ganglia is damaged [ 3 ]. If this condition not treated in time to relieve compression and protect nerve tissue, it will easily lead to limb nerve dysfunction, resulting in sequelae and affecting the prognosis of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, a recent systematic review of all randomized, controlled trials [ 111 ] evaluated the different effects of standard or intensive treatment of BP in patients with ICH. The primary outcomes were mortality at three months, disability based on a modified Rankin scale score, and the combination of death and disability.…”
Section: Resultsmentioning
confidence: 99%